2022
DOI: 10.3390/pharmaceutics14030531
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as Tools to Improve Therapeutic Enzyme Performance

Abstract: The drugs concept has changed during the last few decades, meaning the acceptance of not only low molecular weight entities but also macromolecules as bioagent constituents of pharmaceutics. This has opened a new era for a different class of molecules, namely proteins in general and enzymes in particular. The use of enzymes as therapeutics has posed new challenges in terms of delivery and the need for appropriate carrier systems. In this review, we will focus on enzymes with therapeutic properties and their ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Another alternative consists in the incorporation of lysins in lipid-based systems, such as liposomes, aiming to deliver the loaded lysin to the peptidoglycan layer. Liposomes are spherical structures constituted by one or more phospholipid bilayers, separated by aqueous compartments, which allows them to incorporate hydrophilic or hydrophobic compounds [ 19 , 20 ]. This strategy has demonstrated an improvement to the pharmacokinetic profiles of loaded compounds and, consequently, their therapeutic activity both in vitro and in vivo [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative consists in the incorporation of lysins in lipid-based systems, such as liposomes, aiming to deliver the loaded lysin to the peptidoglycan layer. Liposomes are spherical structures constituted by one or more phospholipid bilayers, separated by aqueous compartments, which allows them to incorporate hydrophilic or hydrophobic compounds [ 19 , 20 ]. This strategy has demonstrated an improvement to the pharmacokinetic profiles of loaded compounds and, consequently, their therapeutic activity both in vitro and in vivo [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that one of the most commonly used methods today is to coat the surface of the liposome with polyethylene glycol (PEG), creating what is known as long-circulating liposomes or 'stealth liposomes'. Obviously, it is possible to further modify the surface of the liposomes by incorporating various ligands onto the surface of the liposome, such as glycoproteins, immunoglobulins, peptides, transferrin, etc., in order to preferentially target them to overexpressed receptors in tumor cells [84].…”
Section: Liposomesmentioning
confidence: 99%
“…Encapsulation of doxorubicin, paclitaxel, or 5-fluorouracil improves their pharmacokinetics, thus increasing their half-life in cancer cells [84][85][86]. Sing et al [86] showed that the encapsulation of DOX and celecoxib (CEL), a non-steroidal anti-inflammatory drug, in liposomes significantly increased the biological activity of chemotherapeutic agents in human skin carcinoma A431 cell culture.…”
Section: Liposomesmentioning
confidence: 99%
“…7 Alternatively, amphiphiles can be used to form vesicles: polymersomes in the case of amphiphilic polymers or liposomes for lipids. 8,9 Using encapsulation, only little enzyme is denatured as it does not interact with the carrier. The effective increase in size and subsequent change in physical properties after encapsulation means the enzymes can be separated by either centrifugation or filtration.…”
Section: Introductionmentioning
confidence: 99%